Exploration of Physics Concepts through the Local Wisdom Traditional Game “Bedil Jepret Bambu” - Muhammad Alif Rahmatulloh; Hafiz Jabbaru Wachid Al Qisnu; Tharisth Natasyavira Izza Arzety (MO.RI Publishing, 2026)
Physics education in Indonesia tends to be abstract, with the connection between physics concepts and students' everyday experiences often remaining unclear. This study maps the physics concepts embedded in the mechanism of the traditional bamboo snap gun (bedil jepret bambu) game as a source of contextual learning. A descriptive qualitative method was employed, based on conceptual analysis of the literature and field data (observation and interviews). The analysis reveals that the mechanism of the bamboo snap gun involves the concepts of elasticity (Hooke's Law), force and acceleration (Newton's Laws), work and energy, impulse and momentum, and parabolic motion. These findings indicate the significant potential of the bamboo snap gun as a physics learning medium that links theory with local cultural contexts. In conclusion, this conceptual mapping can serve as a foundation for developing innovative local-wisdom-based teaching materials to strengthen students' conceptual understanding.